ENETS standardized (synoptic) reporting for neuroendocrine tumour pathology. (14th February 2022) - van Velthuysen, Marie‐Louise F.; Couvelard, Anne; Rindi, Guido; Fazio, Nicola; Hörsch, Dieter; Nieveen van Dijkum, Els J.; Klöppel, Günter; Perren, Aurel
Abstract: In recent years the WHO classification of neuroendocrine neoplasms (NEN) has evolved. Nomenclature as well as thresholds for grading have changed leading to potential confusion and lack of comparability of tumour reports. Therefore, the European Neuroendocrine Tumour Society (ENETS) has set‐up an interdisciplinary working group to develop templates for a pathology data set for standardised reporting of NEN. Experts of various disciplines, members of the ENETS Advisory Board, formed a taskforce that discussed and decided on the structure, content and the number of templates needed for reporting the most common NEN. The selection of the required items was based on the WHO classification of digestive system tumours, the WHO classification of tumours of the lung and mediastinum and on "ENETS standard of care" reports. The final proposal of the working group was approved by the ENETS Advisory Board. Templates for synoptic reporting were created for the seven most common NEN primary sites, that is, stomach, duodenum, jejunum‐ileum, appendix, colon‐rectum, pancreas, lung and mediastinum. In addition, a general template for reporting biopsies was designed. The templates allow the recording of the essential items on differentiation, proliferation (Ki‐67 and mitosis), neuroendocrine features (positivity for chromogranin A and synaptophysin) and stage as well as several optional markers especially helpful for the distinction of neuroendocrine tumours (NET) from neuroendocrine carcinomas (NEC). In summary, this paper presents the content and development of synoptic reports for most sites of NEN by a multidisciplinary team of international experts in the field, which could help to improve unambiguous reporting of NEN. Abstract : This paper reports on the development and content of templates for synoptic reporting of the seven most common NEN primary sites, that is: stomach, duodenum, jejunum‐ileum, appendix, colon‐rectum, pancreas, lung and mediastinum. In addition, a general template for reporting biopsies is designed.